Kinetic Study of Microbial Growth in Anaerobic Digestion of Solid Waste - Mujahid Umar yunus; Kiman Silas; Ali L. Yaumi; Bitrus Highina Kwaji (International Journal of Scientific Multidisciplinary Research, 2023)
Solid waste when discarded to the environment causes serious environmental problems. The kinetic study of microbial growth in anaerobic digestion process is process specific, yet, there are limited reported studies with regards to the feedstock’s (banana peel, chicken dung and waste water treatment sludge). The objective of the study is to carry out the kinetic study of microbial growth, and to know the conditions or environment responsible for the degradation of chicken dung, waste water treatment sludge and banana peel for the production of biogas and biofertilizer. The methodology involves the use of serial dilution, pour plating, cell counting for microbial population and Monod parameters were determined. Microsoft excel 2016 was use to carry out regression analysis, results shows that the maximum, growth rate (????????????????) estimated from the basic Monod equation, of microorganism, was 0.098 hr-1 and the half saturation constant, (????????), 1.2 ×108 mg/l. This pin point the availability of substrate for the survival of microorganisms